TINGKAT KEPUASAN KONSUMEN APOTEK TERHADAP PELAYANAN KEFARMASIAN DI APOTEK KECAMATAN SUKARAME TINGKAT KEPUASAN KONSUMEN APOTEK TERHADAP PELAYANAN KEFARMASIAN DI APOTEK KECAMATAN SUKARAME - Atika Dalili Akhmad; Dirga Dirga; Sudewi Mukaromah K; Nur Adliani; Sukrasno Sukrasno (Jurnal Farmasi Malahayati, 2019)
Health is the main assets in life, one of health care providers is a community pharmacies. Community Pharmacies provide pharmaceutical services and pharmaceutical supplies for the community. The quality of pharmaceutical services should be developed to meet the needs of the community as an effort to improve the welfare of the community. This research method is analytic descriptive with cross sectional survey desaign. This study aims to measure the level of patient satisfaction as the evaluation indicator of the quality pharmaceutical services in community pharmacies. The level of patient satisfaction was measured using a questionnaire with Service Quality (Servqual) model including five dimensions: tangible, reliability, responsiveness, assurance, and empathy. This questionnaire was given to 167 patients in Sukarame District. The questionnaire data were analyzed using Chi-square analysis. The results showed 58.08% of patients were not satisfied with the service given by the community pharmacy. Empathy Dimension (drug information) has the highest satisfaction level (87,83%), whereas reliability dimension having lowest satisfaction level (83,16%). The bivariate test of patient characteristics showed no significant relationship between age (p = 0,310), sex (p = 0,064), education (0.239), occupation (p = 0,439), but monthly income (p = 0,000) and number of patient visits (p = 0,000) had a significant relationship to patient satisfaction.